Mycophenolic Acid for Topical Immunosuppression in Vascularized Composite Allotransplantation: Optimizing Formulation and Preliminary Evaluation of Bioavailability and Pharmacokinetics - Feturi, Firuz G.; Weinstock, Matthias; Zhao, Wenchen; Zhang, Wei; Schnider, Jonas T.; Erbas, Vasil E.; Oksuz, Sinan; Plock, Jan A.; Rohan, Lisa; Spiess, Alexander M.; Ferreira, Lydia M.; Solari, Mario G.; et al. (Frontiers in Surgery, 2018)
Mycophenolic acid (MPA), is the active form of the ester prodrug mycophenolate mofetil (MMF). MMF is an FDA approved immunosuppressive drug that has been successfully used in systemic therapy in combination with other agents for the prevention of acute rejection (AR) following solid organ transplantation (SOT) as well as in vascularized composite allotransplantation (VCA). Systemic use of MMF is associated with gastrointestinal adverse effects. Topical delivery of the prodrug could thus provide graft-targeted immunosuppression while minimizing systemic drug exposure. Our goal was to develop a topical formulation of MPA with optimal in vitro/in vivo characteristics such as release, permeation, and tissue bioavailability to enable safety and efficacy evaluation in clinical VCA. Permeation studies were performed with a solution of MPA (10 mg/ml). In vitro release and permeation studies were performed for different semisolid formulations (Aladerm, Lipoderm, emollient, and VersaBase) of MPA (1% w/w) using a Franz Diffusion Cell System (FDCS). In vivo pharmacokinetic characterization of MPA release from Lipoderm was performed in rats. MPA in solution exhibited a steady state flux (3.8 ± 0.1 µg/cm2/h) and permeability (1.1 × 10−7 ± 3.2 × 10−9 cm/s). MPA in Lipoderm exhibited a steady state flux of 1.12 ± 0.24 µg/cm2/h, and permeability of 6.2 × 10−09 ± 1.3 × 10−9 cm/s across the biomimetic membrane. The cumulative release of MPA from Lipoderm, showed a linear single-phase profile with a R2 of 0.969. In vivo studies with MPA in Lipoderm showed markedly higher local tissue MPA levels and lower systemic MPA exposure as compared to values obtained after intravenous delivery of the same dose of drug (p < 0.05). We successfully developed for the first time, a topical formulation of MPA in Lipoderm with optimal in vitro/in vivo permeability characteristics and no undesirable local or systemic adverse effects in vivo. Our study provides key preliminary groundwork for translational efficacy studies of topical MPA in pre-clinical large animal VCA models and for effectiveness evaluation in patients receiving VCA.